Continuous support during labour in childbirth: a Cross-Sectional study in a university teaching hospital in Shanghai, China - Man Wang; Qing Song; Jun Xu; Zheng Hu; Yingying Gong; Arier C. Lee; Qi Chen (BMC, 2018)
Abstract Background Fear or anxiety could result in adverse consequences on the course of labour. To date, family members are still not permitted in the delivery rooms in the majority of hospitals in China, and continuous support from hospital professional staff is also limited. This study aimed to evaluate the benefits of continuous support by family members and hospital professional staff during labour in China. Methods In this Cross-Sectional study, 362 primiparous pregnancies who self-requested to receive continuous or one to one support with vaginal delivery and 362 primiparous pregnant women with routine hospital maternal care were included from a university teaching hospital. Data on the length of labour, postpartum haemorrhage (PPH), use of pain relief, use of oxytocin, fetal distress, emergency caesarean section and apgar score at 1 and 5 min were retrospectively collected from hospital medical data-base and compared between the two groups. Results Multiple linear regressions adjusting for maternal age, BMI and birth weight, revealed the estimated length of labour for women with routine hospital maternal care was 2.03 times (95%CI 1.86 to 2.21) the duration of women with supportive care (median time, 3.05 h vs 1.5 h). In addition, Fisher's exact test showed the emergency caesarean section rate was significantly lower in women with supportive care compared to women with routine hospital maternal care (3.3% vs 24%). Conclusion Our results suggest that continuous support from family members together with hospital professional staff should be considered as part of intrapartum care in hospitals in China.